2019
DOI: 10.1021/acsearthspacechem.9b00052
|View full text |Cite
|
Sign up to set email alerts
|

Surface Science Investigations of Icy Mantle Growth on Interstellar Dust Grains in Cooling Environments

Abstract: Experimental measurements on the thermal and non-thermal behaviour of water and other simple molecules, including organic compounds such as methanol and benzene, on model interstellar dust grain surfaces and on solid water surfaces using surface science 1 Page 1 of 61 ACS Paragon Plus Environment ACS Earth and Space Chemistry techniques and methodologies are reviewed. A simple qualitative model of the early stages mantle growth arising from a synthesis of the results of such investigations from our own laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 152 publications
1
11
0
Order By: Relevance
“…Our results reinforce the recent proposition from Marchione et al [45] that, in contradiction to the popular Onion model, bare dust grain surface in cold astrophysical environments would be available for other species except water to adsorb onto. The authors base their idea on the experimentally demonstrated agglomeration of H2O molecules on the dust surface [46] that may result in grain surfaces presenting both wet (H2O presents as agglomerates) and dry (absence of H2O) areas.…”
Section: Discussionsupporting
confidence: 90%
“…Our results reinforce the recent proposition from Marchione et al [45] that, in contradiction to the popular Onion model, bare dust grain surface in cold astrophysical environments would be available for other species except water to adsorb onto. The authors base their idea on the experimentally demonstrated agglomeration of H2O molecules on the dust surface [46] that may result in grain surfaces presenting both wet (H2O presents as agglomerates) and dry (absence of H2O) areas.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study of UV irradiation of H 2 /CO codeposited mixtures showed rich chemistry for this system owing to the interaction of an electronically excited CO molecule and the H 2 molecule (Chuang et al 2018). Moreover, very recent results are inverting the trend of considering several onion-like models of cold ices (Marchione et al 2019;Potapov et al 2020). This new set of experiments shows that small icy domains (clusters or islands) are deposited on top of the refractory phase with voids in between.…”
Section: Astrophysical Implicationsmentioning
confidence: 89%
“…However, recent laboratory studies have shown that the bare dust material would be available for the surface processes in cold astrophysical environments. The experiments on the agglomeration of H2O molecules on the dust surface by Rosu-Finsen et al and Marchione et al [47,48] and on the thermal desorption of H2O and CO ices mixed with dust grains by Potapov et al [49,50] clearly demonstrate this finding. Cosmic dust grains may be covered by a submonolayer or few layer quantities of ice due to their fractal nature, high porosity and corresponding large surface area (see ref.…”
Section: Laboratory Astrophysicsmentioning
confidence: 85%
“…Thereafter "thick" ice mantles are generally assumed and atom addition chemistry occurs on the icy mantle surface. However, if the bare dust material in astrophysical environments is available for the surface processes as proposed in [48,50], bare grain surface processes will occur on the full grain lifecycle from the interstellar, protostellar, and protoplanetary phases.…”
Section: Mennella Et Al Irradiated H2o Ices On Hydrogenated Amorphous...mentioning
confidence: 99%
See 1 more Smart Citation